2020
DOI: 10.7554/elife.57784
|View full text |Cite
|
Sign up to set email alerts
|

Breakage of the oligomeric CaMKII hub by the regulatory segment of the kinase

Abstract: Ca2+/calmodulin dependent protein kinase II (CaMKII) is an oligomeric enzyme with crucial roles in neuronal signaling and cardiac function. Previously, we showed that activation of CaMKII triggers the exchange of subunits between holoenzymes, potentially increasing the spread of the active state (Stratton et al. 2014; Bhattacharyya et al. 2016). Using mass spectrometry, we show now that unphosphorylated and phosphorylated peptides derived from the CaMKII-α regulatory segment bind to the CaMKII-α hub and break … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…Intrigued by GHB analogs binding in a specific hub cavity and the functional importance of hub oligomerization for normal CaMKIIα function ( 6 , 7 , 35 ), we investigated a potential effect of the compounds on hub dynamics. Employing a thermal shift assay of the purified CaMKIIα WT hub protein using differential scanning fluorometry, we observed pronounced effects on protein denaturation.…”
Section: Resultsmentioning
confidence: 99%
“…Intrigued by GHB analogs binding in a specific hub cavity and the functional importance of hub oligomerization for normal CaMKIIα function ( 6 , 7 , 35 ), we investigated a potential effect of the compounds on hub dynamics. Employing a thermal shift assay of the purified CaMKIIα WT hub protein using differential scanning fluorometry, we observed pronounced effects on protein denaturation.…”
Section: Resultsmentioning
confidence: 99%
“…Although subunit exchange was minimal under basal conditions, it is possible that the small population of 14-mers/16-mers represented high-energy intermediate states involved in the subunit exchange mechanism. Activation of the CaMKII holoenzyme is thought to destabilize the hub complex, through interactions with the regulatory domain ( Bhattacharyya et al, 2016 ; Karandur et al, 2020 ; Stratton et al, 2014 ). Thus, the 14-mer and 16-mer states could also provide a storage mechanism for pools of potentiated subunits to be released under activating conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of CaMKIIβ kinase activity with different phosphorylation patterns and molecular mechanisms underlying the sleep induction/maintenance activities are currently unknown. Recent studies suggested that the phosphorylation of T305/T306 of CaMKIIα promotes the dissociation of CaMKIIα dodecamer 65 . Another study demonstrated that the same phosphorylation promotes the translocation of CaMKIIα from the spine to dendrite 66 .…”
Section: Discussionmentioning
confidence: 99%